High Prevalence of Leptospira spp. in Rodents in an Urban Setting in Madagascar - Rahelinirina, Soanandrasana (Am J Trop Med Hyg, 2019)
Leptospirosis is a neglected zoonotic bacterial disease caused by pathogenic Leptospira spp. Only limited studies have been conducted on the presence of Leptospira spp. in rats in Antananarivo, the capital city of Madagascar. We assessed Leptospira prevalence in small mammals in urban areas of Antananarivo where sanitation is inadequate and there is risk of flooding during the rainy season. We captured rodents and shrews at two sites and examined kidney samples from 114 animals using culture and a real-time polymerase chain reaction (PCR) assay specific to pathogenic Leptospira spp. We identified 23 positive samples containing Leptospira interrogans and Leptospira borgpetersenii, with a high prevalence in Rattus norvegicus (44.9%). Our results indicate that small mammals, in particular R. norvegicus, present a major public health risk for acquiring leptospirosis in Antananarivo.